Difference between Islamic & conventional banking sector in Bangladesh with regard to customer satisfaction - Sorower, Rabeya Beanta (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015.